Digital Consultation, Information, and Education to Enhance Knowledge and Attitudes on Hypertension - Wulandari, Respati; Sifai, Izzatul Alifah (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2025)
Background: Hypertension is a non-communicable disease known as the silent killer. The majority of deaths from stroke and heart attacks worldwide (more than 1000 cases/hour) are caused by hypertension. This study aims to determine the increase in knowledge and attitudes about hypertension after being given an intervention in the form of digital consultation, information, and education (KIE).Method: The study employed a One-group pretest-posttest design with 36 purposively sampled respondents. It took place in Semarang from November 2023 to January 2024. Digital KIE was the intervention, delivered through WhatsApp flyers over 3 days, facilitated by a healthcare professional. Knowledge and attitudes about hypertension were measured, and data analysis utilized the Wilcoxon test.Result: The average age of respondents was 43.2 (±13.6) years, with a majority being female (75%), having a secondary education (58.3%), employed (77.8%), income > regional minimum wage (63.9%), having a family history of hypertension (63.9%), and not suffering from hypertension (75%). Findings from this study revealed an increase in respondents with good knowledge from 69.4% to 94.4% and respondents with a positive attitude from 61.1% to 80.6%. There was a significant difference in knowledge (Δ = 1; p = 0.000) and respondents' attitudes (Δ = 1.5; p = 0.020) after being provided with hypertension intervention using digital KIE. Digital KIE significantly improves knowledge and attitudes about hypertension. The implementation of digital KIE on a larger scale is expected to be a means of preventing hypertension.